HIV Research Training Partnership of the University of Zambia and Vanderbilt University: Features and Early Outcomes - Wilbroad Mutale; Selestine Nzala; Holly M. Cassell; Marie H. Martin; Benjamin H. Chi; Mulenga Mukanu; Perfect Shankalala; John R. Koethe; Douglas C. Heimburger (Ubiquity Press, 2019)
Background: Despite the burden of HIV being highest in sub-Saharan Africa (SSA), research expertise and capacity to address scientific questions regarding complications of HIV and ART, especially chronic non-communicable conditions, is limited in the region. The comorbidities prevalent in persons with HIV are mediated through diverse mechanisms, many of which can be context or region-specific and are yet to be elucidated. The phenotype, risk factors, and effective interventions for these conditions may differ between populations and settings, and therefore there is an urgent need for research to help understand these processes and how to best address them in SSA. Here, we report the research capacity building activities in SSA conducted by the University of Zambia (UNZA)-Vanderbilt Training Partnership for HIV-Nutrition-Metabolic Research (UVP), drawing lessons and challenges for a wide global health audience. Methods: We reviewed program data and conducted interviews with program leaders and participants to understand and document the progress and outcomes of the partnership. We report the program's early achievements, highlighting drivers and challenges. Results: Between 2015 and 2019, UVP made substantial progress on its goals of training new UNZA PhD scientists to investigate complex nutritional and metabolic factors related to long-term HIV complications and comorbidities. The program has supported 11 UNZA PhD students with dual UNZA-Vanderbilt mentorship; three have graduated, and other candidates are progressing in their PhD studies. The project also supported institutional capacity through UNZA faculty participation in Vanderbilt grant writing workshops, with strong success in obtaining grants among those who participated. UVP also supported development of greater structure to UNZA's PhD program and a mentorship curriculum, both now adopted by UNZA. The major drivers for success included UVP's alignment of goals between UNZA and Vanderbilt, and local institutional ownership. The longstanding history of collaborations between the two institutions contributed substantially to alignment and mutual support of UVP's goals. Several challenges were noted, including limits on direct research funding for students and a relatively small pool of funded investigators at UNZA. Conclusions: Despite some challenges, UVP has achieved positive outcomes over its first four years. Longstanding partnerships and local institutional ownership were the main drivers. We expect the challenges to mitigated as the project continues and produces more UNZA researchers and teams and more funded projects, collectively building the local research community. With continued resources and clear focus, we expect that UNZA's investigators and partners will attract research funding and generate high-impact research outputs across a broad range of studies in HIV as well as newer threats from non-communicable conditions experienced by long-term survivors of HIV and by the general population.